The Current Development and Future Trends of Sustainable Investment in China - Ruan Jiahao (SHS Web of Conferences)
China’s sustainable development goals have significantly accelerated the advancement of sustainable investment, creating a vast and dynamic market with increasing attention from policymakers and stakeholders. In this context, it is particularly necessary to explore the current development status and future trends of sustainable investment to better understand its role in supporting the green transition. The findings indicate that, under strong government support, sustainable investment has made remarkable progress and brought positive environmental and social impacts. Nevertheless, it still faces several challenges, such as the imperfection of policies and regulations, lack of standardization in information disclosure, and relatively low market awareness and investor participation. This research contributes to a deeper understanding of China’s sustainable investment landscape and provides strategic insights for policymakers, financial institutions, and investors. The results are expected to offer valuable reference for promoting long-term, high-quality, and inclusive development in the realm of sustainable finance, while also supporting the design of more effective regulatory mechanisms, the improvement of investor engagement.